Objetos virtuais de aprendizagem como ferramenta metodológica no ensino de genética no ensino médio - Weingärtner, Gilmara de Fatima (2013)
This thesis reflects a theoretical and practical approach about the mediation of technology in teaching and learning of biology. This research was based on authors such as Ausubel, Bachelard and Moran among others. Technological development allows us to use didactic devices in the classroom which provide changes in teaching and learning process. Among those were found Virtual Learning Objects (VLO) that allow an interaction of several medias, images, sound, movement, text, animation which interact with the learner, becoming a more attractive device to the student. This work aimed to evaluate the effect of a didactic sequence with the use of Virtual Learning Objects in the subject of Biology, in the third grade of high school, checking if they can contribute for the improvement of teaching and learning process and the learning of Genetics. For this, the data was collected with 64 students of a public school in Antonio Olinto (Parana – Brazil) and 44 students of a public school in Curitiba (Parana – Brazil) though pretest and posttest questionnaires (Likert Scale). After using the instructional sequence gave up the implementation of post-test and evaluation of VLOs by students. As they considered as more interesting one which allowed greater student action on the object. It was observed that the OVA in question is also the strongest influence on learning, because it refers to the contents of Mendelian Genetics, which showed the biggest difference between the pretest and posttest. It was possible to notice the influence the VLOs had on teaching and learning process, because the provided bigger interaction between student – student, student – teacher and student- content, making a learning process more efficient. Therefore, this research had a positive result for the VLOs as teaching methodology, besides facilitating the comprehension of the concepts covered in classes. Through the answers of the questionnaire applied it can be noticed that the learning level was increased, what shows that the use of the VLO as methodology tool increased the learning, the motivation and the performance of the students sampled.